2007
DOI: 10.1007/s10593-007-0119-5
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxy-2-quinolones 120. Synthesis and structure of ethyl 2-hydroxy-4-oxo-4H-pyrido-[1,2-a]pyrimidine-3-carboxylate

Abstract: the synthesized compounds exist in DMSO solution in the 2-hydroxy-4-oxo form while in the crystal (at least for the case of the unsubstituted derivative) X-ray analysis shows that it occurs in the bipolar 2,4-dioxo form.Interest in 4-oxo-4H-pyrido[1,2-a]pyrimidine derivatives is principally due to their broad spectrum of biological activity. Based on this molecular system there have been synthesized bicyclic diaza sugars which inhibit β-glucosidase with high specificity [2]. 2-(Benzothiazol-2-yl) derivatives a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 8 publications
2
10
0
2
Order By: Relevance
“…Hence, similarly to the previously reported pyridopyrimidine [2], electron impact ionization caused an initial cleavage of the C (4) -N (5) and C (2) -C (3) bonds which also markedly predominates over an alternative break up of the ethoxycarbonyl group in the pyrazinopyrimidine 1 (Sheme 1).…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Hence, similarly to the previously reported pyridopyrimidine [2], electron impact ionization caused an initial cleavage of the C (4) -N (5) and C (2) -C (3) bonds which also markedly predominates over an alternative break up of the ethoxycarbonyl group in the pyrazinopyrimidine 1 (Sheme 1).…”
supporting
confidence: 80%
“…Following a detailed study of the various modifications of carrying out the condensation of 2-aminopyridines with triethyl methanetricarboxylate it was found that the most rational method for preparing ethyl 2-hydroxy-4-oxo-4H-pyrido[1,2-a]pyrimidine-3-carboxylates is to carry out the synthesis in refluxing xylene with a molar reagent ratio of 1:2 [2]. This same method was also used successfully in the preparation of an 8-aza analog of the heterocycles indicated above, namely ethyl 2-hydroxy-4-oxo-4H-pyrazino-[1,2-a]pyrimidine-3-carboxylate (1) which is of interest for the subsequent synthesis of biologically active materials structurally similar to the 4-hydroxyquinol-2-one derivatives extensively studied by us.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These syntheses use commercially S(-)-and R(+)-1-phenyl-and 1-(4-methoxyphenyl)ethylamines from Fluka with the optical purity of at least 99.5 and 99.0%, respectively. The starting ethyl 2-hydroxy-9-methyl-4-oxo-4H-pyrido[1,2-a]pyrimidine-3-carboxylate (2) was synthesized according to the literature procedure [21]. …”
Section: Experimental Partmentioning
confidence: 99%
“…Также как и в аналогичном ранее изученном со-единении [25] в иминопиридиновом фрагменте бицикла наблюдается заметное альтернирова-ние связей: связи Длины связей (Å) в структуре эфира 1 Масс-и ЯМР-спектры хоть и дают важную и полезную информацию о строении эфира 1, но, в отличие от рентгеноструктурного анализа, не по-зволяют так однозначно её трактовать, посколь-ку в принципе не противоречат ни одной из при-веденных таутомерных форм. В частности, сиг-нал протона гидроксильной группы в протонном спектре сильно уширен, что препятствует про-ведению корреляционных экспериментов, а зна-чит и точному установлению его локализации.…”
Section: Issn 2308-8303unclassified